Pelophen B is a non-taxoid binding microtubule-stabilizing agent with promising preclinical anticancer properties - Vermeulen, Stephanie; Ernst, Sam; Blondeel, Eva; Xia, Zihan; Rappu, Pekka; Heino, Jyrki; Dedeyne, Sándor; Denys, Hannelore; Sys, Gwen; Gijsels, Stefanie; Depypere, Herman; Tummers, Philippe; et al. (Springer Science and Business Media LLC, 2025)
Taxanes, such as paclitaxel (PTX), stabilize microtubules and are used as a first-line therapy in multiple cancer types. Disruption of microtubule equilibrium, which plays an essential role in mitosis and cell homeostasis, ultimately results in cell death. Even though PTX is a very potent chemotherapy, its use is associated with major side effects and therapy resistance. Pelophen B (PPH), a synthetic analog of peloruside A, stabilizes microtubules through interaction with a non-taxoid binding site of β-tubulin. We evaluated the anticancer effect of PPH in a variety of tumor types by using established cell lines, early-passage cultures and ex vivo tumor-derived cultures that preserve the 3D architecture of the tumor microenvironment. PPH significantly blocks colony formation capacity, reduces viability and exerts additivity with PTX. Interestingly, PPH overcomes resistance to PTX. Mechanistically, PPH induces a G2/M cell cycle arrest and increases the presence of tubulin polymerization promoting protein (TPPP), inducing lysine 40 acetylation of α-tubulin. Although, results induced by paclitaxel or PPH are concordant, PPH's unique microtubule binding mechanism enables PTX additivity and ensures overcoming PTX-induced resistance. In conclusion, PPH results in remarkable anti-cancer activity in a range of preclinical models supporting further clinical investigation of PPH as a therapeutic anticancer agent.